Uma análise alteral da dignidade humana do preso na Grande Vitória face ao recuperando no modelo APAC-Itaúna: da cegueira ao rosto - Pereira, Cíntia Aparecida Nunes (2010)
Two looks of the Brazilian Penitentiary System (SPB) are argued at present dissertation to the side of the Critical School of the Penal Rights Doctrine and of the ethics and alteridade concepts of Emmanuel Lévinas: The system of the Vitória Metropolitan Zone as a SPB's micro-vision and Protection and Assistance of the Detents Association (Associação de Recuperação e Assistência do Apenado de Itaúna-MG)'s experience as an alternative micro-vision to SPB. Of exploratory atrributes, the investigantion is supported in primary sources, with emphasis in institutional documents and in revision of technical literature about penal and right and dignity. After the analysis of sources data was possible to describe aspects that demonstrate the model superiority APAC for prisoner's recovering. The study approach of the penal rights was complemented by recent researches about the recovering of the prisionery among them: sociology, philosophy and psychology. The study justifies with the necessity to discussion of alternative proposals to the Brazilian Prison System, that is admittedly ineffective regarding the goals of guaranteing for recovering of the prisionary in a health and environment with diginity. Selected the contemporary delimitation of the research, they were used magistrates' speeches and fined as empiric verification elements of the penitentiary system, in the general acceptation, and the alternative proposal of the model APAC. A detachable limitation of the study is the exclusive utilization of public and accessible information to the researchers. By the findings, it was possible to identify empiric evidences that compare the model APAC as a better option to SPB with regard to the: social inclusion of the prisoner, juridical assistance, medical care, physical and worthy psychological terms, cost, relapse, and cooperation between Estado. The model APAC brings to the society a vision that it is possible to break with the social and juridical blindnesses that, supposedly, predestine the country to the shameful act of committing of barbarisms in your penitentiary system.